cDNA cloning and expression analysis of tocopherol cyclase gene from various oil palm tissues (Elaeis guineensis and Elaeis oleifera) - Lai, Mun Seong (2011)
Tocopherol cyclase (TC) which catalyses the formation of γ-tocopherol from reduced (quinol form) 2,3-dimethyl-6-phytyl-1,4-benzoquinone (DMPBQ) is one of the key enzymes in tocopherol biosynthetic pathway. The aim of this study is isolate the cDNA clone encoding TC and to study its expression profile in different oil palm tissues and different developmental stages in the mesocarp. A partial cDNA 0.5 kb in length was amplified using gene-specific primer from an oil palm expressed sequence tags sequence and found to have high sequence identity with other plant species TC such as Oryza sativa (81%) and Helianthus annus (76%) at the amino acid level. Rapid amplification of cDNA ends (RACE) and end to end PCR successfully amplified the cDNA for the full mature protein of TC from two oil palm species (E. guineensis and E. oleifera) of 1. 233 kb in length encoding 411 amino acids. The amino acid identity between the E. guineensis and E. oleifera sequence was 99.6%. Both sequences have three long stretches of hydrophobic residues and 30 carboxylterminal amino acid unique for plants (not found in cynobacteria TC). However, the reported conserved 5 amino acid carboxyl domain KPPGL in plant TC has 1 variant amino acid in both oil palm sequences (RPPGL). Quantitative gene expression analysis performed using Real-time PCR showed expression of E. guineensis TC in mesocarp was moderately high at 7 w.a.a., dropped at 10 w.a.a then increased steadily from 10 w.a.a and reached a maximum level at 17 w.a.a and the expression level dropped significantly at 19 w.a.a. The overall expression levels in leaves were lower than mesocarp with young leaves having a higher expression level than mature leaves. Real-time gene copy number analysis indicated only one copy of TC exists in the oil palm genome. The isolated mature protein sequence of oil palm TC can be used in functional study to understand the vitamin E biosynthetic process in oil palm and plants in general. It can also be used in genetic engineering efforts to modify vitamin E content and composition in plants.